On human worth and excellence - Manetti, Giannozzo (The I Tatti Renaissance library, 2018)
Manetti's account of dignitas and excellentia is covered in four books. The first three books praise the body, the soul and the body/soul composite. Manetti's last book turns from informing an audience to defeating opponents--from persuasion to polemic. He denounces a picture of human life so bleak that death seems better, and he retraces ground explored by the three previous books. The heart of his optimist Christian anthropology is a transcendent ideal, immortality: this is what makes imperfect, embodied humans authentically like a perfect, bodiless God. Other facts about humans show that goodness--also a divine ideal--belongs naturally to them and their earthly world, governed by God with providential care. The natural state of humans is original justice, not original sin, which defiles nature but does not liquidate it. Human life on earth is happy, even joyous, made so by pleasures--including sexual pleasure--that are good and part of God's plan. A sublime piece of God's craftwork is the human body--including the naked body, outside and inside, guts and all--whose image in art is mankind's visible divinity, whether painted on a church wall or carved in antique marble. The art itself--like technology and other vehicles of material culture--manifests human thought in action. Energy, effort, ingenuity and invention are forces of cultural, intellectual and material progress.'Progressive' seems the right word--adjusted for time and place--to use about these attitudes of Manetti's. To call them enlightened is also fair to his ideas about dignitas, which are ideas rooted in antiquity and renewed in the Renaissance, not ideas about the dignity invented in the Enlightenment.--